Knowledge, practice and barriers in surgical site infections prevention among nurses in a Malaysian public hospital - Sham, Fatimah; Mahad, Nor Firziana; Dahalan, Akehsan; Abdul Wahab, Patimah; Fadzi, Nadzirah; Selamat, Hasnah; Haris, Fahni (Universiti Putra Malaysia, 2025)
Introduction: Surgical Site Infections (SSIs) are a significant concern in healthcare, contributing to patient morbidity, prolonged hospital stays, and increased healthcare costs. Nurses play a critical role in the prevention of SSIs through the implementation of evidence-based infection control practices. This study aims to assess the knowledge, practices, and barriers faced by nurses in preventing SSIs, and to explore identify the relationship between their knowledge and practical adherence to preventive measures. Methods: A cross-sectional study was conducted among nurses in a Malaysian public hospital between January and June 2024. Data was collected using a self-administered questionnaire adapted from previous studies, which confirmed its validity and reliability. Spearman’s correlation test was employed to determine the relationship between knowledge and practice. Results: A total of 219 respondents participated in the study, with a mean age of 36.91 years (SD = 5.88). The mean knowledge score was 71.73 (SD = 14.17), with 28.3% demonstrating high knowledge, 21% moderate, and 50.7% low. The mean practice score was 28.58 (SD = 1.86), with 97.3% showing good practices in SSI prevention. No significant correlation between knowledge and practice was found (r = -0.072, p = 0.287). The primary barrier to adherence was an inadequate supply of surgical consumables. Conclusion: Findings revealed that nurses had below-average knowledge in preventing SSIs but demonstrated good adherence to prevention measures. No significant correlation was observed between knowledge and practice. These results highlight the need for targeted interventions to improve both knowledge and practice in SSI prevention among nurses.